The association between maternal HbA1c and adverse outcomes in gestational diabetes - Muhuza, Marie Parfaite Uwimana; Zhang, Lixia; Wu, Qi; Qi, Lu; Chen, Danqing; Liang, Zhaoxia (Frontiers in Endocrinology, 2023)
Background The role of HbA1c in women with gestational diabetes mellitus (GDM) is still unclear, particularly in the Asian population. Aim To investigate the association between HbA1c levels and adverse outcomes considering maternal age, pre-pregnancy body mass index (BMI), and gestational weight gain (GWG) in women with GDM. Method A retrospective study included 2048 women with GDM and singleton live births. Using logistic regression, the associations between HbA1c and adverse pregnancy outcomes were assessed. Result Compared to women with HbA1c ≤ 5.0%, HbA1c was significantly associated with macrosomia (aOR 2.63,95%CI1.61,4.31), pregnancy-induced hypertension (PIH, aOR 2.56,95%CI1.57,4.19), preterm birth (aOR 1.64,95%CI 1.05,2.55), and primary Cesarean section (primary C-section, aOR1.49,95%CI1.09,2.03) in GDM women with HbA1c ≥5.5% while significantly associated with PIH (aOR 1.91,95%CI1.24,2.94) in women with HbA1c 5.1-5.4%. The associations between HbA1c and adverse outcomes varied with maternal age, pre-pregnancy BMI, and GWG. In women aged ≤29 years, there’s significant association between HbA1c and primary C-section when HbA1c was 5.1-5.4% and ≥5.5%. In women aged 29-34 years and HbA1c ≥5.5%, HbA1c was significantly associated with macrosomia. In women aged ≥35 years, there’s significant association between HbA1c and preterm birth when HbA1c was 5.1-5.4% and macrosomia and PIH when HbA1c ≥5.5%. In pre-pregnant normal-weight women, HbA1c was significantly associated with macrosomia, preterm birth, primary C-section, and PIH when HbA1c ≥5.5% while HbA1c was significantly associated with PIH when HbA1c was 5.1-5.4% . In pre-pregnant underweight women with HbA1c 5.1-5.4%, HbA1c was significantly associated with primary C-section. HbA1c was significantly associated with macrosomia among women with inadequate GWG or excess GWG and HbA1c≥5.5%. In women with adequate GWG, there’s significant association between HbA1c and PIH when HbA1c was 5.1-5.4% and ≥5.5% . Conclusion Conclusively, HbA1c at the time of diagnosis is significantly associated with macrosomia, preterm birth, PIH, and primary C-section in Chinese women with GDM.